What Can Sociology Say About Grit? A Cross-Cultural Exploration of the Relationships between Socioeconomic Status, Sense of Control, and Grit - Kwon Hye Won (SAGE Publications, 2022)
Despite growing interest from the public, little attention has been directed toward grit in sociology. By disaggregating grit into its component factors (i.e., perseverance of effort and consistency of interest) on the basis of a measurement test, the author examines the potentially contrasting relations of grit to socioeconomic status. Using survey data from the United States and South Korea, the author finds that those with higher socioeconomic status partially translate their structural advantages into grit, particularly into the perseverance-of-effort dimension of grit in South Korea, via their stronger beliefs in personal control over their lives (i.e., sense of control). This study also reveals a negative association between one’s own or parental education and the consistency-of-interest dimension of grit, suggesting that stick-to-it-iveness can be a potential supplementary psychological resource for those who may lack other resources.